Pengaruh Literasi Keuangan, Pendapatan, dan Gaya Hidup Terhadap Pengelolaan Keuangan Karyawan Catering dan Wedding Organizer (WO) di Kota Bekasi - Razika Nindy Eka Setya; Nugroho, Arif Widodo; Rahmah Putri Wijayanti; Meti Regita Cahyani (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
Financial management is important in maintaining stability, growth and sustainability of financial conditions in yourself and the organization. However, many employees in the Catering and Wedding Organizer (WO) business are still in debt due to the practice of refinement between personal finance and business finance, income differences based on differences in job levels, and lifestyles that follow job demands. This study employs a quantitative methodology, utilizing questionnaires for data acquisition. The analytical procedures encompass Validity Testing, Reliability Testing, Normality Assessment, Multicollinearity Examination, Heteroskedasticity Analysis, Descriptive Statistics, Multiple Linear Regression Analysis, as well as t-tests, F-tests, Multiple Correlation Coefficients, and the Coefficient of Determination (R²). Indicate that financial literacy exerts a positive influence on financial management, whereas income demonstrates a negative effect, and lifestyle exerts a positive impact. Collectively, financial literacy, income, and lifestyle are shown to significantly affect individuals’ capability to manage their finances effectively. This study demonstrates that a high level of financial literacy can support employees in making appropriate financial decisions. With adequate financial literacy, income management becomes more effective, enabling the fulfillment of long-term needs and controlling a consumptive lifestyle, thereby promoting healthier, structured, and sustainable financial management.